Ethical Journalism Adopting the Ethics of Care - Mathewson, Joe (2021)
This book makes the case for the news media to take the lead in combatting key threats to American society including racial injustice, economic disparity, and climate change by adopting an "ethics of care" in reporting practices.Examining how traditional news coverage of race, economics and climate change has been dedicated to straightforward facts, the author asserts that journalism should now respond to societal needs by adopting a moral philosophy of the "ethics of care," opening the door to empathetic yet factual and fair coverage of news events, with a goal to move public opinion to the point that politicians are persuaded to take effective action. The book charts a clear path for how this style of ethics can be applied by today's journalists, tracing the emergence of this empathy-based ethics from feminist philosophy in the 1980s. It ultimately urges ethical news organizations to adopt the ethics of care, based on the human emotion prioritized by Scottish Enlightenment philosopher David Hume, and to pursue a more pro-active, solutions-seeking coverage of current events.This is an invaluable text for students and academics in the fields of journalism ethics, media ethics and media law, as well as for media professionals looking for a fresh perspective on practicing ethical journalism.